Outcomes of Systemic Treatment in Children and Adults With Netherton Syndrome: A Systematic Review - Nouwen, Anouk E. M.; Schappin, Renske; Nguyen, N. Tan; Ragamin, Aviël; Bygum, Anette; Bodemer, Christine; Dalm, Virgil A. S. H.; Pasmans, Suzanne G. M. A. (Frontiers in Immunology, 2022)
Background: Comèl-Netherton syndrome (NS) is a rare disease caused by pathogenic variants in the SPINK5 gene, leading to severe skin barrier impairment and proinflammatory upregulation. Given the severity of the disease, treatment of NS is challenging. Current treatment regimens are mainly topical and supportive. Although novel systemic treatment options for NS have been suggested in recent literature, little is known about their outcomes. Objective: to provide an overview of systemic treatment options and their outcomes in adults and children with NS. Methods: Embase, MEDLINE, Web of Science, Cochrane Central Register of Controlled Trials, and Google Scholar were searched up to July 22, 2021. Empirical studies published in English language mentioning systemic treatment in NS were enrolled. Studies that did not define a treatment period or report at least one outcome were excluded. Methodological quality was evaluated by the Joanna Briggs Institute critical appraisal checklist for case reports or case series. Overall quality of evidence of the primary outcome, skin, was assessed by the GRADE approach. Results: 36 case series and case reports were included. The effects of 15 systemic therapies were described in 48 patients, of which 27 were children. Therapies included retinoids, prednisolone, cyclosporine, immunoglobulins, and biologicals. In retinoids both worsening (4/15 cases) and improvement (6/15 cases) of the skin was observed. Use of prednisolone and cyclosporine was only reported in one patient. Immunoglobulins (13/15 cases) and biologicals (18/21 cases) showed improvement of the skin. Certainty of evidence was rated as very low. Conclusion: NS is a rare disease, which is reflected in the scarce literature on systemic treatment outcomes in children and adults with NS. Studies showed large heterogeneity in outcome measures. Adverse events were scarcely reported. Long-term outcomes were reported in a minority of cases. Nonetheless, a general beneficial effect of systemic treatment was found. Immunoglobulins and biologicals showed the most promising results and should be further explored. Future research should focus on determining a core outcome set and measurement instruments for NS to improve quality of research.